(untitled) (Dissertare, 2016)
Linear Algebra is a branch of mathematics, its teaching and learning is complex, specially, to those careers related to engineering. Generally, it has contents with different abstraction levels; hence, its understanding can be difficult occasionally. Permanent reflections are necessary to find alternatives to mediate in the learning process, especially when the experience is carried out in instructional blended learning environments as current trends in the educational field. Therefore, the aim of this investigation is to generate some theoretical considerations about Linear Algebra learning in a Virtual Learning Environment using Moodle from the perspective of a section of Production Engineering students who shared a blended learning experience at the Centroccidental Lisandro Alvarado University (Venezuela).The research was based on the qualitative approach and interpretive paradigm, using the hermeneutic-dialectic method. In-depth interviews and participant observation were used to collect the information.The initial findings show Linear Algebra through B-learning is a complex dynamic process in which two categories initially interact: progressivity in knowledge generation and gradual opening to virtual experience. The emerging product of this interaction suggests Linear Algebra B-learning requires a whole educational adequacy where the relationship between the difficulty level of the contents and the degree of presence in the classroom must be considered. Thus, a balanced combination between in-class and online activities according to the type and content difficulty are needed in addition to the input characteristics of the participants.